The implementation of the school-based oral English test: a case study / Khairiah Hasni Mohd Kamil - Mohd Kamil, Khairiah Hasni (2008)
Students’ performance in the national examinations has always been used as a yardstick to measure and compare the success of the schools in Malaysia. The emphasis on teaching and learning has geared towards obtaining high results instead of training the students to be responsible for their own learning and to acquire higher level of thinking skills. However, this phenomenon is gradually changing in our education system. School-based assessment has started to gain prominent place in the heart of the examination system as it is believed to provide the stakeholders more accurate results on the actual potentials and abilities of the students. Thus, the school-based assessment is seen as a tool that enables to give fairer judgment to students of various levels of competency. The purpose of this study was to investigate the effectiveness of the implementation of the school-based Oral English Test in Terengganu. Here, the views and perspectives of two school administrators, seven English teachers and thirty students were examined in order to identify the issues and challenges faced. Semi-structured interviews and classroom observations were chosen as methods to conduct this qualitative method study. The findings of the study basically revealed that majority (85.7%) of the English teachers in the school had never attended any OET course organized by the district, state or national level which explains the teachers’ low level competency in handling the oral test effectively. This had resulted to the possibility of producing unreliable scores to the students. To make things worse, those teachers had never been supervised by any Regional Chief Assessor since the implementation of the school-based OET in 2003. Further investigations also revealed that students’ readiness was a crucial factor that led to the ineffectiveness of the school-based assessment. Approximately 83% of the students admitted that they were not fully prepared for the Oral English Test even though they had been given ample of time to prepare by their teachers. The students’ nonchalant attitude was identified to be the main cause. In addition, the environment of the venue of the assessment also played an essential role in the success of this type of assessment. Nearly all of the students agreed that classroom was not a conducive place to conduct the oral test due to its ‘warm’ temperature and noise made by their peers. Generally, the effectiveness of the implementation of the school-based Oral English Test in the school was not fully accomplished. This study is hoped to enlighten the educational stakeholders, especially the education departments and examination boards, to see the flaws of the system and later come up with relevant strategies to upgrade the quality of the school-based assessment so as to be at par with the other school-based assessments implemented in other advanced countries in the world.